Strategies and Challenges in Synchronous and Asynchronous English Learning Activities - Nurdevi Bte Abdul; Maharida Maharida (AL-ISHLAH: Jurnal Pendidikan, 2022)
Technology has a fundamental role in the teaching and learning process, particularly in Covid-19 pandemic situation. This situation forces all the components of education such as teachers, students, and educational practitioners to conduct their role by using technology in English Learning Activities (ELA).  Online learning activities can be conducted synchronously and asynchronously. This study is concerned with exploring students’ strategies and challenges in online English language activities. Observation and semi-structured interview protocol are applied to collect the data. There were 20 students who participated as research subjects of this study. To analyze the data, the researcher applied six analysis steps. It consists of organizing and preparing the raw data, reading through all data, coding the data, interrelating themes/description, and interpreting the meaning of themes/description. The researcher also discussed the literature at the end of the study. It also involves Discourse Analysis approach collaboratively to present the data in extract form. The results of study indicated that students attended learning activities synchronously and asynchronously. Synchronous learning strategies consisted of face to face interaction in zoom, google meet, discussion in room chat, attendance in Google Form or in academic information system. Asynchronous learning strategies covered Google Classroom, Email, and Schoology. The students found challenges in terms of trouble signals, limited internet data, insufficient knowledge on educational technology, and inflexible instructional materials. Thus, it can be stated that online learning activities give promises and challenges to the students.